On the identity of Chunra gigantea Distant (Hemiptera: Cicadellidae), the largest member of the arboreal leafhopper subfamily Idiocerinae - Wei, Cong; Webb, M. D.; Zhang, Yalin (Zootaxa, 2010)
Kuchingella Wei & Webb, gen. n. is established in the leafhopper tribe Megipocerini of the subfamily Idiocerinae, with Chunra gigantea Distant as its type species, based on the description of the male of this species for the first time. The similarity of the new genus to the related genus, Megipocerus Zachvatkin, is discussed. The rostrum of both genera is sexually dimorphic.